Teaching EFL Students’ Speaking Skill Through Digital Storytelling of 9th Grade Students Junior High School: A Case Study Research - Karina Fuzi Rahayu; Evi Karlina Ambarwati; Wahyudin Fitriyana Fitriyana (Institut Agama Islam Negeri Palopo, 2023)
The study aim to improve students' teaching skills by using digital storytelling in teaching speaking for junior high school students. This research used qualitative methodology and case study research as a research design. The participants of this research are 9th-grade students of a public junior high school in Karawang, West Java, Indonesia. The research used a semi-structured observation and interview as instrument of data collection. There are two main findings that the researcher found that answered the purposed research question: 1)How digital storytelling is applied to teach speaking skills and 2)The perception of students after using digital storytelling towards teaching English speaking EFL. So, In conclusion of the research imply that teaching junior high school EFL students digital storytelling can be an effective and entertaining way to improve them speaking skills.Â